Detection of asymptomatic recurrence improves survival of gastric cancer patients. (1st May 2021) - Park, Ji Soo; Choe, Eun‐Ah; Park, Sejung; Nam, Chung Mo; Hyung, Woo Jin; Noh, Sung Hoon; Lee, Seoyoung; Kim, Hyo Song; Jung, Minkyu; Chung, Hyun Cheol; Rha, Sun Young
Abstract: Background: The effect of long‐term surveillance for asymptomatic patients after curative resection of gastric cancer is being debated. We compared the prognosis of Korean patients with recurrent gastric cancer according to the presence or absence of cancer‐related symptoms at the time of recurrence detection. Methods: We retrospectively reviewed the medical records of 305 Korean patients who experienced recurrence after curative resection of primary gastric cancer between March 2002 and February 2017 at Yonsei Cancer Center, Yonsei University College of Medicine, Seoul, Republic of Korea. Results: The median follow‐up duration was 169.8 months (1–267.2), and the median age at first recurrence was 58.1 years (23.4–81.9). Among 305 patients with recurrence, 97 of 231 (42.0%) patients with early recurrence (≤5 years after curative surgical resection) and 47 of 74 (63.5%) patients with late recurrence (>5 years after curative surgical resection) had cancer‐related symptoms at recurrence ( p = 0.001). For survival after recurrence, detection of asymptomatic recurrence was an independent favorable factor (hazard ratio, 0.527; 95% confidence interval, 0.409–0.681; p < 0.001) accompanied with the possibility of subsequent treatment, targeted‐, or immunotherapy for recurrent disease, and locoregional recurrence only. In the late‐recurrence group, the patients with asymptomatic detection of recurrence showed favorable post‐recurrence survival (median, 33.3 months vs. 14.7 months; p = 0.002), overall survival (median, 136.3 months vs. 106.1 months; p = 0.010), and cancer‐specific survival (median, 177.5 months vs. 106.1 months; p = 0.005) than the patients with symptomatic detection. Conclusion: The detection of gastric cancer recurrence in patients without cancer‐related symptoms may be related to improved survival, suggesting the potential benefit of long‐term surveillance. Abstract : Asymptomatic detection of recurrence possibly improved the survival of gastric cancer long‐term survivors after curative surgical resection. The possibility of local control and targeted‐ or immunotherapy for the recurrent disease was related to the favorable survival outcomes. ​